Structural, thermodynamic and digestible properties of maize starches esterified by conventional and dual methods: Differentiation of amylose contents. (October 2018) - Hong, Jing; Zeng, Xin-An; Buckow, Roman; Han, Zhong
Abstract: This work aimed to study esterification of maize starches with four distinct amylose contents including waxy (<1%), normal (23%), Gelose 50 (50%) and Gelose 80 (80%). They were esterified with acetic anhydride via conventional and pulsed electric fields (PEF)-assisted dual modification methods. X-ray diffraction detected the destroyed crystalline area and altered crystalline structure from A-type to B-type of PEF-assisted esterified waxy starch. An obvious decrease in alternative repeating stacks of amorphous and crystalline lamella at q = 0.68 nm −1 and a new 100 interhelix peak at q = 3.90 nm −1 were observed in esterified waxy starch by dual modification. Acetylated starch with 80% amylose content had better glycemic digestibility which included 56.7% resistant starch. Reduced destruction in crystal lamellae resulted in worse thermal stability demonstrated by decreased thermogravimetric rate. In addition, esterified starch granules with smaller amounts of amylose exhibited great change in solubility and show better freeze-thaw stability possessed low syneresis through five freeze-thaw cycles. Graphical abstract: Image 1 Highlights: A-type structure was altered to B-type found in dual esterified waxy starch. New interhelix peak at q = 3.90 nm −1 was observed in dual esterified waxy starch. Higher amylose content exhibited higher RS but lower SDS (esterified G50, 80). PEF had obvious impact on starch with lower amylose content during esterification.